New species of Hasemania (Characiformes: Characidae) from Central Brazil, with comments on the endemism of upper rio Tocantins basin, Goiás State - Bertaco,Vinicius A (2010)
Hasemania kalunga is described from the upper rio Tocantins basin, Chapada dos Veadeiros, Goiás State, Brazil. The new species is distinguished from its congeners by the number of perforated lateral line scales (11-21 vs. 5-9, except from H. crenuchoides and H. piatan), by the presence of a black ver tically-elongate humeral spot (vs. absent, except from H. crenuchoides, H. nambiquara, and H. piatan), and by absence of scale sheath along anal-fin base (vs. presence, except from H. maxillaris, and H. piatan), by 19 principal caudal-fin rays (vs. 18 in H. piatan). It differs also from H. crenuchoides by morphometric data. The absence of scale sheath covering the anal-fin base, an uncommon character in Characidae, and the endemism of the ichthyofauna from the upper rio Tocantins are discussed.